Assessment of cardiovascular risk and target organ damage among adult patients with primary hypertension in Thika Level 5 Hospital, Kenya: a criteria‐based clinical audit. Issue 2 (10th June 2013) - Mwita, Clifford Chacha; Akello, Walter; Sisenda, Gloria; Ogoti, Evans; Tivey, David; Munn, Zachary; Mbogo, David
Abstract Background Appropriate management of hypertension reduces the risk of death from stroke and cardiac disease and includes routine assessment for target organ damage and estimation of cardiovascular risk. However, implementation of evidence‐based hypertension management guidelines is unsatisfactory. We explore the use of audit and feedback as a quality improvement (QI) strategy for reducing the knowledge practice gap in hypertension care in a resource poor setting. Aims The aim of this study is to determine the level of compliance to evidence‐based guidelines on assessment of cardiovascular risk and target organ damage among patients with hypertension in Thika Level 5 Hospital in central Kenya and to implement best practice with regard to evidence utilisation among clinicians in the hospital. Method A retrospective clinical audit done in three phases spread over 5 months. Phase one involved identifying five audit criteria on assessment of cardiovascular risk and target organ damage in patients with hypertension and conducting a baseline audit in which compliance to audit criteria, blood pressure control and drug prescription practices were assessed. Phase two involved identifying barriers to compliance to audit criteria and strategies to overcoming these barriers. The third phase was a follow‐up audit. Results There was no use of a cardiovascular risk assessment tool in both audits (0% vs. 0%; P = 1.00). Testing urine for haematuria and proteinuria reduced from 13% to 8% (P = 0.230) while taking a blood sample for measuring blood glucose, electrolytes and creatinine levels improved from 11% to 17% (P = 0.401). Performance of fundoscopy and electrocardiography remained unchanged at 2% and 8%, respectively (P = 0.886 and P = 0.898). High patient load was identified as the biggest barrier to implementation of best practice. Blood pressure control improved from 33% to 70% (P ≤ 0.001), whereas the proportion of patients on two or more recommended antihypertensive drugs rose from 59% to 72% (P = 0.158). Conclusion In Thika Level 5 Hospital, audit and feedback has a poor impact on assessment of cardiovascular risk and target organ damage but positive impact on blood pressure control and prescription practices. Time and sample size may have affected observed results. Additional audits and alternative QI strategies are warranted.